Pemafibrate Pretreatment Attenuates Apoptosis and Autophagy during Hepatic Ischemia-Reperfusion Injury by Modulating JAK2/STAT3β/PPARα Pathway - Ziqi Cheng; Chuanyong Guo (PPAR Research)
Hepatic ischemia-reperfusion injury (HIRI) is a common phenomenon in liver transplantation and liver surgery. This article is aimed at clarifying the role of pemafibrate in HIRI through JAK2/STAT3β/PPARα. In the experiment, we divided Balb/c into seven groups, namely, normal control (NC), Sham, PEM (1.0 mg/kg), IRI, IRI + PEM (0.1 mg/kg), IRI + PEM (0.5 mg/kg), and IRI + PEM (1.0 mg/kg). We used biochemical assay, histopathological evaluation, immunohistochemistry, RT-PCR and qRT-PCR, ELISA analysis, and other methods to determine the level of serum AST, ALT, IL-1β, and TNF-α in the liver at three time points (2 h, 8 h, and 24 h) after reperfusion of apoptosis factor, autophagy factor, and the JAK2/STAT3/PPARα content in tissues. Our experiment results showed that the pemafibrate can effectively reduce the level of hepatic IR injury. In addition, pemafibrate has anti-inflammatory, antiapoptotic, and antiautophagy effects, which are mediated by the JAK2/STAT3β/PPARα pathway.